Assessment of Shoulder Joint Strength Disproportion of Masters Swimmers - Aleksander Wiażewicz; Jerzy Eider (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
The aim of this study was to find out whether Masters class swimming affects strength disproportion and if there is a correlation between the length of sport swimming training in Masters swimmer’s past (SST) and strength parameter’s deficits? Eighteen Masters category swimmers affiliated in Szczecin Masters Team (178.3 ±2.28 m; 77.9 ±2.86 kg) participated in the study. Isokinetic strength measurement was made on Biodex S4 dynamometer. Subjects performed shoulder flexion/extension moves: 3 repetitions – 60 deg/sec and 20 repetitions – 180 deg/sec. Following values were used: peak torque (PT), maximal repetition work (MRW), coefficient of variation (COV), total work (TW), average power (AP), agonist to antagonist ratio (AG:AN). None of the investigated variables were statistically significant in side to side comparison. All of the parameters were higher in extension. Also, no statistically significant difference between sides in AG:AN. Moderate positive correlation was found between SST and PT deficit in extension movement (0.420). Also low positive correlation between SST and PT deficit in flexion (0.396), and MRW deficit in extension (0.352). Masters class swimming did not affect side strength disproportion or agonist to antagonist differences. However, it is possible that swimming training in other categories does.